2010
DOI: 10.1063/1.3508949
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmonic controllable enhanced emission from the intrachain and interchain excitons of a conjugated polymer

Abstract: We demonstrate selectively enhanced emission by controlling the intrachain and interchain excitons of a conjugated polymer through adjusting surface plasmons. Enhanced light emission from the intrachain excitons was observed by coupling the localized surface plasmon resonance with the intrachain band of the conjugated polymer using Ag nanoparticles. Light emission from the interchain excitons was enhanced by exploiting both the increased strength of the interchain dipole due to the image dipole and the couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Surface-plasmon resonance induced by the oscillation of the charge density of conduction electrons, and its corresponding electromagnetic field can strongly affect the optical properties of any semiconductor nanoparticles nearby.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Surface-plasmon resonance induced by the oscillation of the charge density of conduction electrons, and its corresponding electromagnetic field can strongly affect the optical properties of any semiconductor nanoparticles nearby.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, the poor light extraction efficiency of $20% in a conventional OLED limits the external quantum efficiency due to the total internal reflection (TIR) at the glass substrate/air and indium-tinoxide (ITO)/substrate interfaces, the waveguide (WG) mode at the organic/ITO anode interface, and the surface plasmon (SP) losses at the metallic cathode/organic interface. [7][8][9][10] Various methods have been proposed to enhance light out-coupling in OLEDs, including surface microstructures on ITO anode to reduce the WG mode loss, 11,12 photonic crystals or microlens arrays attached on the glass substrate for the reduction of TIR, 13,14 corrugated cathode to reduce SP losses, [15][16][17][18] optical microcavity structures, 19 and so on. Recently, the localized SP effect excited by metallic nanostructures is becoming one of the most attractive approaches for light emission enhancement in OLEDs through the coupling with localized SP resonance and the emission energy.…”
mentioning
confidence: 99%
“…Recently, the localized SP effect excited by metallic nanostructures is becoming one of the most attractive approaches for light emission enhancement in OLEDs through the coupling with localized SP resonance and the emission energy. [15][16][17][18]20,21 For example, Koo et al have demonstrated the enhancement of light extraction efficiency in OLEDs by a quasi-periodic buckling structure without introducing spectral changes and directionality. 15 The roughness on the cathode side induced by lithography process 16 or template transform 15 can match the momentum of SPs and radiated light, leading to the SP enhancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the photophysics of interchain and intrachain interactions can be applied to polymer Thin-film field-effect transistors (TFTs), because mobility is limited by interchain rather than intrachain transport [18]. In a previous paper, we reported the achievement of selectively enhanced emission by controlling the intrachain and interchain excitons of MEH-PPV films through adjustment of surface plasmons [19]. In this paper, we present the results of picosecond TR-PL spectroscopy studies on SP mediated MEH-PPV films.…”
mentioning
confidence: 99%